Attack rates of human papillomavirus type 16 and cervical neoplasia in primiparous women and field trial designs for HPV16 vaccination. Issue 1 (1st February 2000) - Kibur, M; Geijerstamm, V Af; Pukkala, E; Koskela, P; Luostarinen, T; Paavonen, J; Schiller, J; Wang, Z; Dillner, J; Lehtinen, M
Abstract : Background: Identification of human papillomavirus type 16 (HPV16) as the major risk factor for cervical neoplasia, and mass production of DNA free HPV capsids have paved the way to preventive vaccination trials. Design of such trials requires reliable attack rate data. Objective: Determination of (1) HPV16 and (2) cervical neoplasia attack rates in primiparous women. Estimation of actuarial sample sizes for HPV16 vaccination phase IV trials. Design: A longitudinal cohort study. Methods: Population based Finnish Maternity Cohort (FMC) and Finnish Cancer Registry (FCR) were linked for the identification of two cohorts of primiparous women: (1) a random subsample of the FMC: 1656 women with two pregnancies between 1983–9 or 1990–6 and living in the Helsinki metropolitan area, and (2) all 72 791 primiparous women living in the same area during 1983–94. Attack rate for persistent HPV16 infection (1) was estimated in 1279 seronegative women by proportion of seroconversions between the first and the second pregnancy. Comparable 10 year cumulative incidence rate (CR) of cervical intraepithelial neoplasia grade III and cervical cancer (CIN III+) (2) was estimated based on cases registered at the FCR during 1991–4. Results: The HPV16 attack rates were 13.8% (<18 years), 7.0% (18–19 years), 2.3% (21 years), 2.4% (23 years), and 4.5% (<25 years). Number of vaccinees required for a 5 year efficacy trial with persistent HPV16 infection as the end point ranged between 1000 and 3900, assuming 80% power, 90%–70% vaccine efficacy (VE), and misclassification. The CRs of CIN III+ were 0.33% (<18 years), 0.44% (18–19 years), 0.21% (20–24 years), and 0.28% (<25 years). Number of vaccinees required for a 10 year efficacy trial with HPV16 positive CIN III+ as the end point was 15 000 assuming 80% power, 90% VE, and 75% aetiological fraction of CIN III+ for HPV16. Conclusions: The attack rates of HPV16 and CIN III+ identify primiparous women under 25 years of age among target populations for postnatal HPV vaccination at phase II/III trials.